Opera at the bandstand : then and now - Martin, George Whitney (Scarecrow Press, 2014)
In his book, Opera at the Bandstand: Then and Now, George W. Martin surveys the role of concert bands during the nineteenth and early twentieth centuries in making contemporary opera popular. He also chronicles how in part they lost their audience in the second half of the twentieth century by abandoning operatic repertory.